Financial Performance Analysis of PT Mandala Multifinance Tbk and PT Clipan Finance Indonesia Tbk In 2023 (International Journal of Economics Management and Social Science, 2025)
This study aims to analyze the financial performance of two Indonesian finance companies, PT Mandala Multifinance Tbk (MFIN) and PT Clipan Finance Indonesia Tbk (CFIN), in 2023. The analysis was conducted using three main ratio groups: solvency ratios, activity ratios, and profitability ratios. Secondary data was obtained from annual financial reports published on the Indonesia Stock Exchange. The results show that MFIN has superior performance in terms of operational efficiency and profitability, while CFIN exhibits a more conservative capital structure but has weaknesses in the effectiveness of asset and receivables management. This study provides a comparative overview of the financial health of multifinance companies, which can serve as a reference for investors, management, and other stakeholders